2010
DOI: 10.1681/asn.2010030280
|View full text |Cite
|
Sign up to set email alerts
|

Hemofiltration and Hemodiafiltration Reduce Intradialytic Hypotension in ESRD

Abstract: Symptomatic intradialytic hypotension is a common complication of hemodialysis (HD). The application of convective therapies to the outpatient setting may improve outcomes, including intradialytic hypotension. In this multicenter, open-label, randomized controlled study, we randomly assigned 146 long-term dialysis patients to HD (n ϭ 70), online predilution hemofiltration (HF; n ϭ 36), or online predilution hemodiafiltration (HDF; n ϭ 40). The primary end point was the frequency of intradialytic symptomatic hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
204
5
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 244 publications
(226 citation statements)
references
References 28 publications
11
204
5
6
Order By: Relevance
“…It was recently shown that the application of convective therapy was associated with better intradialytic hemodynamic stability. 19 Other aspects, such as quality of life, erythropoietin resistance, vascular stiffness, left ventricular mass, nutritional status, and cost utility, are currently under investigation as predefined secondary endpoints of this study. 20,21 The strengths of our study are its randomized design and the accurate and concise data collection.…”
Section: Discussionmentioning
confidence: 99%
“…It was recently shown that the application of convective therapy was associated with better intradialytic hemodynamic stability. 19 Other aspects, such as quality of life, erythropoietin resistance, vascular stiffness, left ventricular mass, nutritional status, and cost utility, are currently under investigation as predefined secondary endpoints of this study. 20,21 The strengths of our study are its randomized design and the accurate and concise data collection.…”
Section: Discussionmentioning
confidence: 99%
“…Such investigations may focus on patient sodium exposure from dialysate and diet or other strategies to mitigate IDWG. Current studies are looking at biofeedback or medication to control BP during dialysis, dialysate cooling, and increasing the frequency of dialysis to lower ultrafiltration rates and volumes (4,(24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…Although these studies were designed to evaluate outcomes of arterial blood pressure and intrasession symptoms, no differences were observed in presession P levels, and no superiority of HF compared to HDF was observed. 19,20 Since the end of the 1990s, a new hemodialytic method was introduced that employed three types of depuration: convection; adsorption by resins; and diffusion. 21 An ultrafiltrate is formed by the plasma water leaving the convective filter, and it is conveyed into a cartridge containing adsorbents (polystyrenic resin), which retain various high molecular-weight toxic substances.…”
Section: Convective Hemodialysis Techniquesmentioning
confidence: 99%